2005
DOI: 10.1021/je0501484
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and Viscosity Properties of α-Amino Acids and Their Groups in Aqueous Sodium Caproate Solutions

Abstract: Densities and viscosities have been measured for solutions of DL-R-valine or DL-R-leucine in aqueous sodium caproate solutions at 298.15 K and 308.15 K. On the basis of these data, the apparent molar volumes (V m,2 ), standard partial molar volumes (V°m ,2 ), standard volumes of transfer (∆ t V°), hydration number (n H ), and viscosity B-coefficients of DL-R-valine and DL-R-leucine have been determined. Combined with the corresponding data of glycine, DL-R-alanine, and DL-R-amino-n-butyric acid reported recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
3
14
0
1
Order By: Relevance
“…This indicates that with increasing hydrocarbon chain length of the carboxylate ion, the dehydration effect increases. The same observation has also obtained for ␣-amino acids [14] and glycyl dipeptides [18] in aqueous sodium carboxylate solutions.…”
Section: Peptidessupporting
confidence: 81%
See 1 more Smart Citation
“…This indicates that with increasing hydrocarbon chain length of the carboxylate ion, the dehydration effect increases. The same observation has also obtained for ␣-amino acids [14] and glycyl dipeptides [18] in aqueous sodium carboxylate solutions.…”
Section: Peptidessupporting
confidence: 81%
“…Sodium carboxylate containing the large-size anions is known to influence the dissociation of proteins in solutions [4]. The effect of some alkali metal and alkaline earth metal carboxylates on the physico-chemical properties of amino acids has been studied by some workers [5][6][7][8][9] and our group [10][11][12][13][14] in order to understand the fine details of the interactions of the protein with carboxylate salts. In recent years, we have carried out the investigations on thermodynamic properties of some small peptides in aqueous sodium carboxylate solutions [15][16][17][18] because small peptides contain more complex structure and more components of proteins than amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity studies of some amino acids and peptides have been reported for alkali chlorides [3], KSCN [4,5], NH 4 Cl [6], urea [7], sodium butyrate [8], sodium acetate [9,10], tetra-n-alkylammonium bromide [11,12], caffeine [13], sodium caproate [14], MgCl 2 [15], NaC 6 [16], CaCl 2 [17], magnesium acetate [18], tetramethyl ammonium iodide [19], Cu II nitrate and Ni II chloride [20], surfactant [21], methanol [22], d-glucose [23], potassium citrate salt solutions [24], and KCl and KNO 3 solutions [25]. Kumar et al [11,26,27] have reported the effect of NaBr, KCl, KBr, MgCl 2 , and Na 2 SO 4 on viscosity values of some amino acids and glycylglycine.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few measurements on the interactions between amino acids and organic salts [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%